La afectividad como recurso docente en el proceso de enseñanza-aprendizaje - RENGEL, PAOLA; Loor Rivadeneira, Ruth; Naranjo, Mercedes; Narváez Olmedo, Gabriela (Revista Ecos de la Academia, 2021)
Affectivity in the teaching-learning process is an essential factor to positively influence students throughout the educational process, because students would learn to manage their emotions and those of others, giving teachers back the place main example of life for children and adolescents, mainly. The objective of the study was to know the impact that affectivity has as a teaching resource in the teaching-learning process. The methodology used was with a qualitative approach with a case study design in a group of students and teachers through instruments made by the author such as classroom observation, teacher survey and student interview. The results revealed that not all the investigated teachers know about the importance of affectivity and the positive effects of using it, however, those who, if they have it clearly, recognize its importance, but do not use it thinking of it as an educational resource . This is how teachers need to complete several characteristics to be affective teachers, leading from the way they reach their students through a positive attitude, innovative learning strategies and constant motivation within the classroom. Finally, a strategy guide is proposed for teachers about affectivity as a teaching resource.
Keywords: Keywords: Affectivity, teaching-learning process, teaching resource